1989
DOI: 10.1055/s-2007-1009267
|View full text |Cite
|
Sign up to set email alerts
|

Increased Synthesis of Prolactin and Growth Hormone during Incubation in the Pituitary of Broody Nagoya Hens

Abstract: Synthesis and release rates of prolactin and growth hormone (GH) in the anterior pituitary of laying and incubating broody chickens (Nagoya breed) were determined by a disc electrophoretic technique after in vitro incubation of anterior pituitaries with a labeled amino acid. Prolactin synthesis and release were two-fold higher in incubating than in laying hens, resulting in twofold increase in the concentration of prolactin in the gland. GH synthesis was three-fold higher in incubating than in laying hens but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A role for PRL in inducing avian parental behavior was first observed when injections of PRL induced rearing behavior in domestic chickens (Riddle et al, 1935). Thereafter, high circulating PRL concentrations were found to be associated with rearing behavior in chickens (Hoshino and Wakita, 1989;Lea et al, 1981;Sharp et al, 1979Sharp et al, , 1988, turkeys (Burke and Dennison, 1980;Proudman and Opel, 1981), mallard ducks (Boos et al, 2007;Goldsmith and Williams, 1980), swans (Goldsmith, 1982), native Thai chickens (Chaiyachet et al, 2013b), and ring doves (Buntin, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A role for PRL in inducing avian parental behavior was first observed when injections of PRL induced rearing behavior in domestic chickens (Riddle et al, 1935). Thereafter, high circulating PRL concentrations were found to be associated with rearing behavior in chickens (Hoshino and Wakita, 1989;Lea et al, 1981;Sharp et al, 1979Sharp et al, , 1988, turkeys (Burke and Dennison, 1980;Proudman and Opel, 1981), mallard ducks (Boos et al, 2007;Goldsmith and Williams, 1980), swans (Goldsmith, 1982), native Thai chickens (Chaiyachet et al, 2013b), and ring doves (Buntin, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant evidence has linked maternal behavior in several avian species with increased PRL secretion. High PRL levels are known to be associated with brooding behavior in chickens (Sharp et al, 1979(Sharp et al, , 1988Bedrak et al, 1981;Lea et al, 1981;Hoshino and Wakita, 1989), turkeys (Burke and Dennison, 1980;Proudman and Opel, 1981), mallard ducks (Goldsmith and Williams, 1980;Boos et al, 2007), and swans (Goldsmith, 1982). The studies in which broody chickens (Sharp et al, 1979), ducks (Goldsmith and Williams, 1980), and swans (Goldsmith, 1982) have been allowed to hatch and rear the young have shown that PRL concentrations decline at the end of the incubation period.…”
Section: Introductionmentioning
confidence: 99%
“…However, we cannot exclude higher rates of GH turnover both within the hypophysis and the blood which might be associated with incubation behaviour. In support of the latter, Hoshino and Wakita (1989) observed a greater than three-fold increase in the synthetic rate of GH associated with incubation behaviour, whereas the rate of release was suppressed.…”
Section: Rna Dot Blot Analysismentioning
confidence: 64%
“…(Scanes, 1987), and short-term fasting results in increased GH secretion in young chickens (Scanes, 1987) and turkeys (Proudman and Opel, 1981). Since incubation behaviour is associated with aphagia and a 20-30% decrease in body weight (Zadworny et al, 1985(Zadworny et al, , 1988, it has been proposed by Hoshino and Wakita (1989) (fig 3). Similar results have been reported in the chicken (Kansaku et al, 1994).…”
Section: Rna Dot Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation